Trinidad cocoa - opening the pods and extracting the beans. - (:unkn) unknown (My University, 2011)
A picture of labourers on a cocoa estate preparing the cocoa beans for transportation by donkeys to the cocoa houses for drying and fermentation.
Colour: Black and white; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cocoa; Cocoa trade; Labourers